Analisis Pengaruh Konsentrasi KCl dan Polyamine Terhadap Swelling Clay Berdasarkan Uji Liner Swell Meter - Theo Abraham Kumayas; Baiq Maulinda Ulfah; Jamaluddin Jamaluddin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Wellbore instability caused by swelling clay represents a major technical challenge in drilling operations. This study aims to analyze and compare the effectiveness of Potassium Chloride (KCl) as an inorganic shale inhibitor and Polyamine as an organic polymer inhibitor in suppressing the swelling rate of reactive clay minerals. The experimental method was conducted in the laboratory using a Linear Swell Meter (LSM) for 24 hours with inhibitor concentration variations of 1%, 3%, and 5%. The test results indicated that KCl demonstrated significantly superior performance compared to Polyamine in controlling clay expansion. The final swelling value of KCl decreased significantly with increasing concentration, from 42.30% (1% concentration) to 22.35% (5% concentration), due to the ability of K+ ions to enter the interlayer space and suppress hydration. Conversely, Polyamine was less effective, with swelling values remaining high above 35% across all concentrations (35.89% at 5% concentration), as its mechanism is limited to surface encapsulation without optimally arresting crystal expansion. In conclusion, KCl at a 5% concentration provides the best formation stability and is highly recommended to minimize the risk of wellbore instability in reactive clay formations.